Farhana Qazi, Secrets of the Kashmir Valley - Ms. Maryam Zubair (CISS Insight Journal, 2016)
Much has been written about Jammu and Kashmir dispute between India and Pakistan, but little literature exists exclusively on the role of women in Kashmiris’ fight for freedom. Farhana Qazi documents this aspect of the freedom movement in Kashmir in Secrets of the Kashmir Valley. The word “Secrets” in the title aptly describes a reality that seldom gets the attention it deserves, i.e; the struggle of women in the Jammu and Kashmir conflict The author has narrated her personal experiences of meetings with numerous women involved in the Kashmiri struggle. The inspiration for her venture into the subject comes from her mother and maternal grandmother. The first two chapters, ‘Mama’s War’ and ‘Remembrance’ are a narrative of the Kashmiri struggle as seen through the eyes of her mother and grandmother, the latter being a Kashmiri herself and the former identifying strongly with the Kashmir cause and was involved in politics in her youth.